Pengaruh Kecerdasan Emosional Terhadap Akhlak Siswa Kelas V SD Negeri Tunggak III Tahun 2014/2015 - MEGANINGRUM, Dra. Ratnasari Diah Utami, M.Si (2015)
his study aims to determine the effect of emotional intelligence on the character class student V SDN Stumps III. The population in this study were all students of class V Elementary School Stumps III in 2014/2015 which amounted to 34 students. Data collection techniques used are questionnaires, observations and interviews. The analysis technique used is a simple regression analysis that preceded the analysis prerequisite test that normality test and liniaritas. Based on the results of data analysis is concluded. 1). simple regression equation is Y = 39 443 + 0,490X, meaning that emotional intelligence affects the character of students. This is evident from the results of the direction coefficient of the regression coefficients of The variables emotional intelligence (b) is equal to 0.490, so it can be expressed emotional intelligence variables affect the morals of students. 2). The second hypothesis test result of emotional intelligence (b) is equal to 0.490 or positive, the obtained> ie 3.822 2.035 at significance level of 5%. Data from the analysis of data obtained by the coefficient of determination (R2) of 31.3%. The conclusion from this study is that there is a significant pengarug between emotional intelligence to character Elementary School fifth grade students Stumps III sebasar year 2014/2015 31.3%